دور المصارف التجارية في تمويل المشروعات الصغيرة والمتوسطة في الاقتصاد الليبي - الشافعي أ. الشافعي إبراهيم; اوصيلةأ. سميرة حسين (Aljameai, 2022)
الملخص: هدفت الدراسة إلى معرفة الدور الذي تلعبه المصارف التجارية في تمويل المشروعات الصغيرة والمتوسطة، وبيان واقع المشروعات الصغرى والمتوسطة في ليبيا، وقد تم إتباع المنهج الوصفي التحليلي، وتمثل مجتمع الدراسة في موظفي المصارف التجارية العاملة بمدينة الخمس والمتمثلة في فروع مصرف الجمهورية، حيث بلغ عددهم (80) موظف، وقد استجاب منهم (66)، بنسبة استجابة (83%) واستخدم برنامج spss الإحصائي لتحليل البيانات، وقد تم التوصل الى عدة نتائج اهمها: أن هناك دور للمصارف التجارية في دعم وتمويل المشروعات الصغرى والمتوسطة، وان المصارف التجارية تتساهل في تقديم التمويل اللازم لتنفيذ المشروعات الصغيرة والمتوسطة، كما تعمل المصارف التجارية على تقديم الاستشارات الفنية التي تخص نشاط المشروعات الصغيرة والمتوسطة التي تدعمها. Abstract: The study aimed at the role that commercial banks play in financing small and medium enterprises, the reality of small and medium enterprises in Libya, and the consequent reduction in unemployment. The study relied on the descriptive and analytical approach, and in order to achieve its objectives, a questionnaire was designed through which the required data were collected and distributed to employees of commercial banking banks, and the researcher relied on the use of the jpss statistical program package on the number of also using statistical methods, the arithmetic mean of the standard deviation, method (T- test) to choose the validity of the study hypothesis and the recommendations of the study to a number of results, the most important of which is that there is a contribution to commercial banks in supporting and financing small and medium enterprises, and the study also reached a set of recommendations, the most prominent of which is the definition of the importance of financing for small and medium-sized enterprises, which can reduce unemployment.